2021
DOI: 10.1007/s43465-021-00407-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Radiographic Indexes for Elbow Stability Assessment: Part A—Cadaveric Validation

Abstract: Introduction Elbow bony stability relies primarily on the high anatomic congruency between the humeral trochlea and the ulnar greater sigmoid notch. No practical tools are available to distinguish different morphotypes of the proximal ulna and herewith predict elbow stability. The aim of this study was to assess inter-observer reproducibility, evaluate diagnostic performance and determine responsiveness to change after simulated coronoid process fracture for three novel elbow radiographic indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…A shallow trochlear notch may be caused by coronoid process fractures; however, since coronoid process fractures may be overlooked, parameters are measured on plain radiographs of the elbow joint to reduce these oversights. In a study using fresh-frozen cadaver specimens of upper limbs from human donors, Luceri et al found that the ACI decreased from 1.90 prior to a fracture to 1.58 following a fracture of the coronoid process, and the TDI decreased from 0.45 prior to a fracture to 0.39 following a fracture [ 10 ]. A study by Kilgus et al reported that the elbow instability group showed a significantly larger opening angle (94.1° vs. 88.5°) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A shallow trochlear notch may be caused by coronoid process fractures; however, since coronoid process fractures may be overlooked, parameters are measured on plain radiographs of the elbow joint to reduce these oversights. In a study using fresh-frozen cadaver specimens of upper limbs from human donors, Luceri et al found that the ACI decreased from 1.90 prior to a fracture to 1.58 following a fracture of the coronoid process, and the TDI decreased from 0.45 prior to a fracture to 0.39 following a fracture [ 10 ]. A study by Kilgus et al reported that the elbow instability group showed a significantly larger opening angle (94.1° vs. 88.5°) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two primary indices and two derived angles comprising the Anterior Coverage Index (ACI), Trochlear Depth Index (TDI), Proximal Ulnar Bow (PUB), and Radiographic Opening Angle (ROA) were measured on lateral elbow radiographs ( Figure 1 ) [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…For radiographic evaluation of shoulder joint and elbow joint, the craniocaudal, caudocranial, mediolateral, and lateromedial positions were proposed to this study (Aryana et al, 2021; Knox et al, 2003; Luceri et al, 2021; Vandevelde et al, 2006). Upon consideration, the lateromedial and caudocranial positions were not considered for further analysis, as it was difficult to position the organism in these positions.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in our study by the moderate ICC for the RCA measurements and the low strength of the correlation between TDI and RCA (expected r value = 1). The authors recommend, therefore, to rely on linear measurements and, if needed, to obtain derived angles to describe GSN coverage or sigmoid notch opening by mathematical operations, such as RCA = 4 • arctang (2 • BD / AC) = 4 • arctang (2 • TDI) and sigmoid notch opening angle = RCA / 2 [31].…”
Section: Discussionmentioning
confidence: 99%